Bacteriological Evaluation of Tonsillar Surface and Tonsillar Core Micro Flora in Patients Undergoing Tonsillectomy (Health Renaissance, 2016)
Background: Acute tonsillitis is the most common disease for the ENT surgeons. Effective treatment of the tonsillitis depends on knowledge of the infecting organism but there is always a dilemma whether the antibiotics prescribed for the tonsillitis is sufficient for the different organisms in the surface and core of the tonsils.Objective: To study the microorganism on the surface and in the core of the tonsil among the patients undergoing tonsillectomy and to correlate clinical profile of the patients with various microorganisms isolated.Methods: This was a cross sectional study conducted on fifty patients’ age ranging from 3 years to 45 years. The swabs obtained from the surface of the tonsil prior to tonsillectomy and core of the tonsil post tonsillectomy were sent for isolation of micro organism and microbial susceptibility technique by standard microbial method.Results: The common age group for tonsillitis was below 15 years (n= 26) and having male predominance and more common in patients from hilly region. The commonest indication for tonsillectomy was recurrent tonsillitis (n=47). There was 82% similarity in microorganisms isolated from the surface and core of the culture. Conclusion: This study highlights that the culture from the surface of the tonsil reflects the organism in the core. Staphylococcus aureus was the commonest isolated organism in the surface and core of the tonsil.Health Renaissance 2014;12(3): 149-153